SUNGGINGAN WAYANG KULIT MBAH NIMAN DESA CINYAWANG KABUPATEN CILACAP - Salim Salim (Canthing, 2021)
The main thing that is interesting to know about the form of wayang kulit, is the technique of making and carving leather puppets which are complex is the coloring. Coloring in wayang is the most important factor. Due to the color of the shadow puppets, there is a soul of the shadow puppet character, as was done by mbah Niman from Cinyawang village, Cilacap district. This research begins with the problem, how are the techniques and process of coloring the wayang kulit purwa by Mbah Niman and the second, how is the aesthetic aspect of the color of the puppet purwa by Mbah Niman. The purpose of this study was to describe and explain the techniques and aesthetic values contained in the shadow puppet colors by Mbah Niman